Selection of Plus Trees and their Progeny Testing in Eucalyptus Hybrid - Sidhu, D. S. (Indian Forester, 1993)
The study was undertaken with the aim to initiate tree improvement programme in Eucalyptus hybrid. Plus trees were selected in plantations at farmer’s field with comparison tree method. Only those trees were selected as plus trees which had height more than 20 per cent; diameter more than 35 per cent; and volume more than 150 per cent over the average of their respective comparison trees. Thirty one plus trees were selected and of them only 16 were progeny tested in nursery along with control. Eleven progenies excelled, one equalled and four were below the control in seedling height. A maximum of 51.3 per cent more height than the control was observed in the progeny of plus tree number 17. The progenies recorded highly significant differences among themselves. Four of the progenies were significantly above and one was significantly below the control. The information obtained from progeny testing is useful in eliminating the poor performing progenies from field testing programmes.